Practical implementation of information flow in Paragon - Nazir, Javed (My University, 2012)
Paragon is a newly developed language by the security research group of Chalmers University of Technology, Sweden. The major task of my thesis work is practical implementation of a real world problem in Paragon. I have chosen mental poker game to implement in Paragon. Another part of my thesis work is to compare Paragon with Jif, with respect to how convenient implementation is in the two languages, and how well Paragon achieves the goal of improving on the limitations of Jif. After implementating the case study in Paragon, and comparing Paragon and Jif, I conclude that Paragon is able to provide more precise guarantees than Jif.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Systemvetenskap, informationssystem och informatik; Data- och systemvetenskap; Information & Communication Technology; Computer and Information Science; Information Systems; Computer and systems science